FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK UMKM (Studi Kasus UMKM di Kabupaten Demak) - Khiyang Mudayanto, 14.05.52.0209; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2018)
This study aims to examine empirically the influence of knowledge and understanding of tax laws, service tax officers, tax sanctions, and level of trust in the system of government and law on compliance of taxpayers compliance SMEs.The population in this study is the UMKM taxpayers in Demak City as much 110 SMEs located in 5 Districts, Demak Kota District, Karang Anyar District, Karang Tengah District, Mijen District and Sayung District. The method used is Convenience Sampling method.The result of this research is service of tax apparatus have positive effect to taxpayer compliance of SMEs. Knowledge and understanding of tax laws, service tax officers, tax sanctions, and level of trust in the system of government and law have no effect the compulsory compliance of SMEs. Keywords: Taxpayer Knowledgeand Understanding of Tax Laws, Service Tax Officers, Tax Sanctions, and Level Of Trust in the System Of Government and Law, Compliance of SMEs Tax Payers.